Clinically ill patients' experiences of early mobilisation after liver transplantation: a qualitative study using Pender's health promotion model. Issue 1 (18th January 2023) - Zhong, Lixia; Jin, Yanhong; Gu, Yanmei; He, Wenjing; Zheng, Yulin; Yang, Tongnan; Li, Yingying; Fu, Li; Zhang, Weiwei; Xu, Qiuying
Abstract : The aim of this study is to explore the factors influencing early mobilisation behaviours and patients' needs in critically ill patients after liver transplantation (LT). This interview study used phenomenological research, and Pender's health promotion model (HPM) was used to construct the interview guide. With the use of purposeful sampling, a total of 19 critically ill patients who experienced early mobilisation after LT were recruited at three tertiary hospitals in Beijing from August to November 2022. Data were collected through semi-structured interviews and analysed using Colaizzi's seven-step method. Nine themes were categorised into the three domains of Pender's HPM. The first domain was individual characteristics and experiences: (1) symptoms of end-stage liver disease limiting premobility behaviours and (2) previous treatment experience affecting understanding of early mobilisation after LT. The second domain was behaviour-specific cognition and affect: (3) coexistence of benefits and concerns in early mobilisation after LT, (4) barriers to early mobilisation after LT, (5) high self-efficacy in early mobilisation after LT, (6) individual differences in early mobilisation and (7) support and encouragement from family, wardmates and medical staff. The final domain was behavioural outcomes: (8) the need for sufficient staff, a quiet environment, safety, goals, guidance and family participation and (9) a strong willingness to comply with early mobilisation plans. The three areas and nine themes extracted in this study are helpful for the long-term development of early mobilisation in patients after LT.